Weight-Loss Cognitive-Behavioural Treatment and Essential Amino Acid Supplementation in a Patient with Spinal Muscular Atrophy and Obesity - Marwan El Ghoch; Paola Vittoria Bazzani; Simona Calugi; Riccardo Dalle Grave (Case Reports in Medicine)
Spinal muscular atrophy is a genetic neuromuscular disease characterised by muscle atrophy, hypotonia, weakness, and progressive paralysis. Usually, these patients display increased fat mass deposition and reductions in fat-free mass and resting energy expenditure—an unfavourable condition that facilitates the development of obesity. However, weight management of these patients remains poorly described. Hence, the aim of this case report was to describe the clinical presentation and weight management of a 31-year-old male patient with spinal muscular atrophy type III, class I obesity, and metabolic syndrome treated for 1 year by means of a personalised multistep cognitive-behavioural treatment for obesity. The treatment produced a weight loss of 7.2 kg (7.1%), which was associated with a marked improvement in both the patient’s self-reported general conditions and obesity-related cardiometabolic profile, and no adverse effects in terms of spinal muscular atrophy (i.e., reductions in fat-free mass or resting energy expenditure).